The Role of the Notary in Drafting Authentic Deeds for Syndicated Financing at Sharia Rural Bank Harta Insan Karimah Parahyangan, Indonesia - Ghadamfar Muflih Idroes; Yanis Rinaldi; Ika Susilawati (Graha Primera Saintifika, 2025)
Sharia syndicated financing refers to the distribution of a large amount of funds by several financial institutions to a single debtor, involving many parties and complex agreements. In this arrangement, the notary plays a vital role as the official authorized to draw up authentic deeds in order to guarantee legal certainty and legal protection. However, explicit regulations are lacking concerning the role, authority, and responsibilities of notaries, particularly in syndications between Islamic Financial Institutions and conventional financial institutions. Existing regulations remain general and do not specifically address the execution of notarial duties in such contexts, leading to potential invalidity of deeds and increased risks of legal liability. This study aims to explain the role of the notary in drafting authentic deeds for syndicated financing at PT. BPRS Harta Insan Karimah Parahyangan and to identify obstacles and solutions in its practice. The research adopts a juridical-empirical method with a statutory approach, employing literature review and interviews. The results show that the notary not only drafts the deed, but also serves as a legal advisor and formulates the structure of agreements in accordance with positive law and Sharia principles. The obstacles encountered include the need for Sharia certification, the complexity of documents, time and human resource constraints. Solutions include enhancing notarial competence, applying prudential principles, and improving the quality of human resources. It is recommended that the government formulate a national guideline for Sharia syndicated financing and that notaries continue to develop their expertise in this field.